When gastric point-of-care ultrasound is indeterminate: an educational review and suggested reporting framework - Stephen C Haskins; Cristian Arzola; Yuriy Bronshteyn; Hari Kalagara; David Hardman; Oliver Panzer; Marissa M Weber; Eric Heinz; Jan Boublik; Javier Cubillos; Nadia Hernandez; Joshua Zimmerman; et al. (Regional Anesthesia & Pain Medicine, 2026)
Gastric point-of-care ultrasound (POCUS) is increasingly used to support aspiration-risk assessment when fasting history, comorbidities, medication exposure, or procedural urgency make clinical assessment uncertain. Its value depends on more than identifying gastric contents when images are clear. A useful examination must be attempted, completed, interpreted, and connected to a safe clinical decision. This article uses a focused secondary analysis of the 65 studies included in the original narrative review of gastric POCUS in medically complex patients to examine how indeterminate and non-interpretable examinations are reported. In the 65-study narrative-review evidence base, 32 studies reported at least one indeterminate or non-interpretable examination, 24 reported no or zero such examinations, and nine had unclear or non-numeric reporting. The main reporting concern is that studies often do not clearly identify scans that were not performed, scans that were started but not completed, images that were technically inadequate, results that were uncertain despite visualization, and interpretable diagnostic findings. Clinically, an indeterminate gastric POCUS examination is non-diagnostic and should cause the clinician to either rely on the original aspiration-risk assessment and management plan or choose a more cautious plan when the clinical situation warrants. A clearer reporting pathway can make future gastric POCUS studies easier to interpret, compare, teach, and apply safely.